Structural, Textural, and Thermal Propertiesof Freeze-thawed Quick-frozen Cooked Rice PSB Rc 18 (Oryza sativa L.). - Dollete, Una Grace M.; Azanza, Maria Patricia V.
The study characterized the quality properties of freeze-thawed quick-frozen intermediate amylose cooked rice PSB Rc 18 (Oryza sativa L.). Scanning electron microscopy (SEM), texture profile analysis (TPA), and differential scanning calorimetry (DSC) were employed to monitor structural, textural, and thermal properties including retrogradation in quick-frozen rice as subjected to 1, 3, and 5 freeze-thaw cycles (FTCs) (?18 °C for 16 h; 10 °C for 8 h). Data from SEM, TPA, and DSC explained progressive deteriorative quality changes with increasing FTC. The SEM micrographs revealed the formation of honeycomb structures. The TPA results showed significant (p < 0.05) increase in hardness, cohesiveness, chewiness, springiness; as well as a decrease in adhesiveness. The DSC analysis demonstrated the decreasing trend of thermal transition temperatures. Based on the obtained results, it is recommended that quick-frozen cooked rice should not be exposed to more than 3 FTCs.